Identification of Cellular Pathogenicity Markers for SIL1 Mutations Linked to Marinesco-Sjögren Syndrome - Gatz, Christian; Hathazi, Denisa; Münchberg, Ute; Buchkremer, Stephan; Labisch, Thomas; Munro, Ben; Horvath, Rita; Töpf, Ana; Weis, Joachim; Roos, Andreas (Frontiers in Neurology, 2019)
Background and objective: Recessive mutations in the SIL1 gene cause Marinesco-Sjögren syndrome (MSS), a rare neuropediatric disorder. MSS-patients typically present with congenital cataracts, intellectual disability, cerebellar ataxia and progressive vacuolar myopathy. However, atypical clinical presentations associated with SIL1 mutations have been described over the last years; compound heterozygosity of SIL1 missense mutations even resulted in a phenotype not fulfilling the clinical diagnostic criteria of MSS. Thus, a read-out system to evaluate reliably the pathogenicity of amino acid changes in SIL1 is needed. Here, we aim to provide suitable cellular biomarkers enabling the robust evaluation of pathogenicity of SIL1 mutations. Methods: Five SIL1 variants including one polymorphism (K132Q-SIL1), three known pathogenic mutations (V231_I232del-SIL1, G312R-SIL1 & L457P-SIL1) and one ambiguous missense variant (R92W-SIL1) were studied along with the wild-type proteins in Hek293 in vitro models by cell biological assays, immunoprecipitation, immunoblotting and immunofluorescence as well as electron microscopy. Moreover, the SIL1-interactomes were interrogated by tandem-affinity-purification and subsequent mass spectrometry. Results: Our combined studies confirmed the pathogenicity of V231_I232del-SIL1, G312R-SIL1 and L457P-SIL1 by showing instability of the proteins as well as tendency to form aggregates. This observation is in line with altered structure of the ER-Golgi system and vacuole formation upon expression of these pathogenic SIL1-mutants as well as the presence of oxidative or ER-stress. Reduced cellular fitness along with abnormal mitochondrial architecture could also be observed. Notably, both the polymorphic K132Q-SIL1 and the ambiguous R92W-SIL1 variant did not elicit such alterations. Study of the SIL1-interactome identified POC1A as a novel binding partner of wild-type SIL1; the interaction is disrupted upon the presence of pathogenic mutants but not influenced by the presence of benign variants. Disrupted SIL1-POC1A interaction is associated with centrosome disintegration. Conclusions: We developed a combination of cellular outcome measures to evaluate the pathogenicity of SIL1 variants in suitable in vitro models and demonstrated that the R92W-SIL1 missense variant is a polymorphism rather than a pathogenic mutation leading to MSS.